Ultra Performance Liquid Chromatography Method for Fluticasone Propionate - DALVI, P.; FILMWALA, Z.; VISHNU BANE, TUSHAR (Asian Journal of Chemistry, 2010)
A simple, rapid, sensitive, gradient reverse phase ultra performance liquid chromatographic method involving ultraviolet detection (UPLCUV) was developed for analysis of fluticasone propionate and it's impurities in nasal spray pharmaceutical formulation. It was carried out on a waters Acquity BEH C18 (1.7 μm, 100 mm × 2.1 mm) column using methanol:ammonium acetate:acetonitrile (50:35:15) as mobile phase A and methanol:acetonitrile (50:15) as mobile phase B at a flow rate of 0.250 mL/min and a 239 nm detection. Results showed that ultra performance liquid chromatography exhibited a rapid, sensitive and separation efficiency superior to that of existing conventional HPLC method.